Measurement of cycle-resolved engine-out soot concentration from a diesel-pilot assisted natural gas direct-injection compression-ignition engine. (March 2022) - Kheirkhah, Pooyan; Kirchen, Patrick; Rogak, Steven
Exhaust-stream particulate matter (PM) emission from combustion sources such as internal combustion engines are typically characterized with modest temporal resolutions; however, in-cylinder investigations have demonstrated significant variability and the importance of individual cycles in transient PM emissions. Here, using a Fast Exhaust Nephelometer (FEN), a methodology is developed for measuring the cycle-specific PM concentration at the exhaust port of a single-cylinder research engine. The measured FEN light-scattering is converted to cycle-resolved soot mass concentration (C m ), and used to characterize the variability of engine-out soot emission. To validate this method, exhaust-port FEN measurements are compared with diluted gravimetric PM mass and scanning mobility particle sizer (SMPS) measurements, resulting in close agreements with an overall root-mean-square deviation of better than 30%. It is noted that when PM is sampled downstream in the exhaust system, the particles are larger by 50–70 nm due to coagulation. The response time of the FEN was characterized using a "skip-firing" scheme, by enabling and disabling the fuel injection during otherwise steady-state operation. The average response time due to sample transfer and mixing times is 55 ms, well below the engine cycle period (100 ms) for the considered engine speeds, thus suitable for single-cycle measurements carried out in this work. Utilizing the fast-response capability of the FEN, it is observed that cycle-specific gross indicated mean effective pressure (GIMEP) andC m are negatively correlated (R 2 : 0.2–0.7), implying that cycles with lower GIMEP emit more soot. The physical causes of this association deserve further investigation, but are expected to be caused by local fuel-air mixing effects. The averaged exhaust-portC m is similar to the diluted gravimetric measurements, but the cycle-to-cycle variations can only be detected with the FEN. The methodology developed here will be used in future investigations to characterize PM emissions during transient engine operation, and to enable exhaust-stream PM measurements for optical engine experiments.